2023
DOI: 10.1515/eng-2022-0433
|View full text |Cite
|
Sign up to set email alerts
|

Study of the behavior of reactive powder concrete RC deep beams by strengthening shear using near-surface mounted CFRP bars

Abstract: The applications of modern materials especially reactive powder concrete for improving concrete structures have been significantly growing in recent years. Great conduct properties creep, shrinkage, little permeability, ultra-high strength, and expanded safety against corrosion are the important features of Reactive Powder Concrete. In addition, the use of the Near-Surface Mounted technique in recent decades has helped strengthen and repair shears-reinforced concrete (RC) for deep beams using carbon fiber repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A. [1] on deep beams reinforced with carbon fiber tensile reinforcement and reactive powder concrete, and the results showed that the cracks on the surfaces of the deep beams reinforced with reactive powder concrete were effectively suppressed. Zhelyazov T. [2] tested the flexural reinforcement of reinforced concrete beams in coastal areas using basalt with basalt fiber-reinforced polymer (BFRPS), and the results showed that, although the modulus of elasticity of BFRP reinforcement was lower than that of structural steel, the increase in loadcarrying capacity increased with pretensioning.…”
Section: Introductionmentioning
confidence: 99%
“…A. [1] on deep beams reinforced with carbon fiber tensile reinforcement and reactive powder concrete, and the results showed that the cracks on the surfaces of the deep beams reinforced with reactive powder concrete were effectively suppressed. Zhelyazov T. [2] tested the flexural reinforcement of reinforced concrete beams in coastal areas using basalt with basalt fiber-reinforced polymer (BFRPS), and the results showed that, although the modulus of elasticity of BFRP reinforcement was lower than that of structural steel, the increase in loadcarrying capacity increased with pretensioning.…”
Section: Introductionmentioning
confidence: 99%